Hydrophobic fluorocarbon-modified silica aerogel tubular membranes with excellent CO2 recovery ability in membrane contactors. (15th September 2015) - Lin, Yi-Feng; Chang, Jun-Min; Ye, Qian; Tung, Kuo-Lun
Graphical abstract: Highlights: Silica aerogels were successfully coated onto Al2 O3 tubular membrane supports. These as-prepared silica aerogel tubular membranes are not only durable but also reusable. CO2 recovery using the silica aerogel tubular membranes is increased to almost 100%. These silica aerogel tubular membranes show promise for large-scale CO2 capture in power plants. Abstract: In this study, the pore size of macroporous Al2 O3 tubular membranes were successfully shrunk by the coating of mesoporous silica aerogels on their surface. Fluoroalkylsilane (FAS) was successfully grafted on the surface of silica aerogel tubular membranes, resulting in a hydrophobic surface on the resulting membranes. The CO2 absorption flux of the FAS-modified silica aerogel tubular membrane reaches a stable value of approximately 0.6 mmol/m 2  s in one day of operation. Furthermore, the as-prepared FAS-modified silica aerogel tubular membranes can be used continuously to absorb CO2 for at least one day, and they can be reused in three consecutive cycles of CO2 absorption. The results of this study demonstrated that these FAS-modified silica aerogel tubular membranes are not only durable but also reusable. The CO2 gases are almost absorbed completely (97% CO2 recovery) at liquid and gas flow rates of 500 and 200 sccm, respectively. Thus, these as-prepared silica aerogel tubular membranes with FAS modifications show promise for use in a large-scale CO2 absorption in a power plant.